Familial hypercholesterolemia: A systematic review of modeling studies on screening interventions. (August 2022) - Jahn, Beate; Santamaria, Júlia; Dieplinger, Hans; Binder, Christoph J.; Ebenbichler, Christoph; Scholl-Bürgi, Sabine; Conrads-Frank, Annette; Rochau, Ursula; Kühne, Felicitas; Stojkov, Igor; Todorovic, Jovan; James, Lyndon; et al.
Abstract: Background and aims: FH is still underdiagnosed. Cost-effectiveness results of preventive screening strategies vary. We aimed at systematically assessing the benefits, harms and cost effectiveness of screening for familial hypercholesterolemia (FH) and at providing an overview of the main characteristics and methodological approaches of applied decision-analytic models. Methods: A systematic literature search was conducted in MEDLINE, EconLit, CRD-databases and the CEA-registry for FH screening starting 2012. Earlier studies were included from a published systematic review. Results were reported in standardized semi-quantitative evidence tables. Costs were converted to current euros. Incremental cost-effectiveness ratios (ICERs) were recalculated according to economic guidelines. Results: Out of our 211 retrieved studies, eight were included in the review in addition to six studies from an earlier review. Studies were conducted in Europe (UK, The Netherlands, Spain, Poland), USA and Australia evaluating cascade (CS), opportunistic (OS), universal screening (UniS), or combinations using genetic testing, clinical criteria or combinations. Studies evaluating only CS identified strategies with an ICER of up to 37, 100 EUR/quality-adjusted life-year (QALY) but some strategies were dominated depending on test combinations. UniS of newborns in combination with CS had an ICER≤15, 000 EUR/QALY for sequential cholesterol-genetic screening. In other studies, UniS was dominated by OS/CS. Conclusions: Our systematic review demonstrates the values of FH screening and provides an overview of potentially relevant screening strategies to be tested using a decision-analytic model for the respective country or region. Future research is needed on the transferability of results to other countries and modeling spillover effects to newborns. Graphical abstract: Image 1 Highlights: Familial hypercholesterolemia is still underdiagnosed even if various screening strategies have been investigated/applied. Many cascade-screening programs appear to be cost effective (at threshold <40, 000 EUR/quality-adjusted life-year gained). There is no consistent evidence on cost effectiveness of universal screening and opportunistic screening. Future research is needed on transferability to other countries and modeling spillover effects to newborns.